Oxidative stress mechanisms caused by ag nanoparticles (NM300K) are different from those of AgNO3: effects in the soil invertebrate enchytraeus crypticus - Ribeiro, Maria J. (2015)
The mechanisms of toxicity of Ag nanoparticles (NPs) are unclear, in particular in the terrestrial environment. In this study the effects of AgNP (AgNM300K) were assessed in terms of oxidative stress in the soil worm Enchytraeus crypticus, using a range of biochemical markers [catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), glutathione reductase (GR), total glutathione (TG), metallothionein (MT), lipid peroxidation (LPO)]. E. crypticus were exposed during 3 and 7 days (d) to the reproduction EC20, EC50 and EC80 levels of both AgNP and AgNO3. AgNO3 induced oxidative stress earlier (3 d) than AgNP (7 d), both leading to LPO despite the activation of the anti-redox system. MT increased only for AgNP. The Correspondence Analysis showed a clear separation between AgNO3 and AgNP, with e.g. CAT being the main descriptor for AgNP for 7 d. LPO, GST and GPx were for both 3 and 7 d associated with AgNO3, whereas MT and TG were associated with AgNP. These results may reflect a delay in the effects of AgNP compared to AgNO3 due to the slower release of Ag+ ions from the AgNP, although this does not fully explain the observed differences, i.e., we can conclude that there is a nanoparticle effect.